Triangular extension of hinge flaps: A novel technique to resolve stomal stenosis and prevent restenosis in staged buccal mucosal urethroplasty. (6th May 2021) - Azuma, Ryuichi; Horiguchi, Akio; Ojima, Kenichiro; Shinchi, Masayuki; Aizawa, Tetsushi; Tsuchiya, Masato; Nakayama, Eiko; Nagano, Hisato; Ito, Keiichi; Asano, Tomohiko; Kiyosawa, Tomoharu
Abstract : Objectives: To verify the utility of triangular extension of a hinge flap in buccal mucosal staged urethroplasty to resolve stomal stenosis after the first stage and ultimately prevent restenosis. Methods: A total of 23 patients (triangular extension group) were studied in 2013–2019. In the first stage, buccal mucosa was transplanted, and an extended triangle portion of the mucosa was placed beside the proximal and/or distal stoma that was created when the stricture segment of the urethra was resected. In the second stage, during tubularization of the urethral plate, an incision was made at the stoma to increase the caliber to which the triangular extension was inserted. The procedure was considered successful when a 17‐Fr flexible cystoscope passed through the reconstructed urethra at 6 months after the second‐stage urethroplasty and no additional surgery or bougie dilation required. The clinical course of the triangular extension group was compared with 24 patients who underwent conventional staged urethroplasty (control group). Results: In total, 20 patients from each group underwent second‐stage surgery. No patients in the triangular extension group required additional revision surgery because of stomal stenosis after first‐stage surgery, whereas five (20%) control patients did. Urethroplasty was successful in 19 patients (95%) in the triangular extension group and in 19 patients (95%) in the control group. Uroflowmetry after the second‐stage surgery indicated that the mean maximum urinary flow rate was 21.5 and 15.8 mL/s after triangular extension and the control procedure, respectively ( P  = 0.027). Conclusions: The triangular extension technique reduces the need for revision surgery and prevents postoperative restenosis.